(untitled) (Perner’s Contacts, 2016)
Commercial air transport began to assert itself more effectively in the 20s. Since this time has the entire market environment changed. Nowadays air service is operated in a framework of international agreements, which are implemented into national laws and regulations, where airlines decide about services to offer, to which clients and at prices. Strong competitive environment is positively reflected in the offer of services for passengers and price decline. Airlines had to adapt to trends and from this arose the concept of low-cost airlines. Conversely, traditional companies are becoming increasingly integrated in global alliances and increase the sphere of activity.